(untitled) (The International Journal for Scientific Research, 2025)
Background: Thalassemia is a genetic condition that requires at least one parent to be a carrier, this condition is inherited. Certain types of blood diseases are characterized by frequent transfusions of blood, including sickle cell disease, anemia, and thalassemia. Blood transfusions offer many advantages, but they might cause the body to store too much iron. Extra iron in the body can lead to serious complications. Eliminating excess iron may reduce the risk of certain disorders. IpJade (deferasirox) is a medication used to treat chronically high iron levels in the body caused by frequent blood transfusions. Objective: The aim of the present study is to identify the safety and efficacy of deferasirox locally manufactured product in iron chelation of hemoglubinopathic patients in Iraq. Patients and Methods: This study was done at the Children’s Educational Hospital / Hemoglobinopathy center in Karbala. 100 patients’ medical records were acquired randomly who were diagnosed with B-thalassemia Major between the ages of 5 to 27. The information recorded included whether the patient was male or female, the daily dose of Deferasirox prescribed for each patient, and common side effects the patients were experiencing, as well as hepatic and renal function biomarkers. Results: The results obtained from this study showed slight changes in some biomarkers (WBC, AST, serum ferritin) while clear and strong changes in other (ALT. Alkaline phosphate, serum creatinine) before and after the treatment. The findings of this study revealed a statistically association between the serum creatinine and Deferasirox doses in addition to hepatic enzymes. Conclusion: This study revealed that the iron chelating agent (Deferasirox) is proven to be the best for patient compliance due to its favored administration compared to other types, it is shown to be well tolerated and efficacious in patients despite some negative effect which need periodic monitoring.